Trust, Security, and Online Purchase Intention in Home Appliances: Moderating Role of Digital Literacy - Fadisty Ailsa Putri; Gallang Perdhana Dalimunthe (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of trust and security on online purchase intention in purchasing home appliance products through e-commerce, as well as to examine the moderating role of digital literacy. This study applied a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to 160 respondents who had experience purchasing home appliance products through e-commerce platforms. The findings show that trust and security have a positive and significant effect on online purchase intention. In addition, digital literacy does not significantly moderate the relationship between trust and online purchase intention, but it significantly strengthens the relationship between security and online purchase intention. The study concludes that trust and security remain critical determinants of online purchase intention in e-commerce, while digital literacy plays a selective moderating role, particularly in strengthening security perceptions. This study is limited by its sample size and focus on respondents from a specific consumer segment, which may affect generalizability. This study contributes to consumer behavior, digital marketing, and e-commerce literature by extending understanding of purchase intention in the home appliance sector. The findings also provide practical insights for e-commerce platforms, marketers, and business practitioners in designing strategies that improve consumer trust, transaction security, and digital engagement.